An analysis of cetylpyridinium chloride (CPC) by FESEM, EDX methods, and its applications - Yadav, Chandradip Kumar; Adhikari, Majoj Kumar; Maharjan, Jasana; Bhattarai, Ajaya (Rajarshi Janak University Research Journal, 2024)
Cetylpyridinium chloride (CPC) is a potential cationic surfactant with cleansing and antimicrobial properties. Apart from its use as an emulsifying and cleansing agent, it is used in cosmetics, industrial processes, pharmaceuticals, food additives, etc. In the present study, the purity of cetylpyridinium chloride (CPC) was determined using FE-SEM and EDX methods. The FE-SEM test showed CPC sizes from 46.35μm to 77.76μm. The result and analysis of EDX depicted the purity of the sample. The percentage of elements present in cetylpyridinium chloride has been explained by EDX data. The percentages of C, N, and Cl were found to be 87.4, 5.4, and 7.2 percent respectively by weight.